Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1128/aac.02034-18
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Gel Component Hydroxyethyl Cellulose Significantly Enhances the Infectivity of Chlamydia trachomatis Serovars D and E

Abstract: The transmission of the urogenital serovars of Chlamydia trachomatis can be significantly influenced by vaginal gels. Hydroxyethyl cellulose is a commonly used gelling agent that can be found in vaginal gels. Hydroxyethyl cellulose showed a concentration-dependent growth-enhancing effect on C. trachomatis serovars D and E, with a 26.1-fold maximal increase in vitro and a 2.57-fold increase in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Incorporating microbicides into vaginal gels is a well-accepted strategy for inhibiting sexually transmitted disease transmission including HSV-2 transmission [9][10][11]. We also showed that even basic components of the vaginal gels, such as the gelling agent hydroxyethyl cellulose can also significantly influence the replication of sexually transmitted pathogens such as Chlamydia trachomatis [12].…”
Section: Introductionmentioning
confidence: 81%
“…Incorporating microbicides into vaginal gels is a well-accepted strategy for inhibiting sexually transmitted disease transmission including HSV-2 transmission [9][10][11]. We also showed that even basic components of the vaginal gels, such as the gelling agent hydroxyethyl cellulose can also significantly influence the replication of sexually transmitted pathogens such as Chlamydia trachomatis [12].…”
Section: Introductionmentioning
confidence: 81%
“…The titer of infectious elementary bodies (EBs) was determined by indirect immunofluorescence assay and was expressed in inclusion forming unit/mL (IFU/mL) [18]. HeLa cells were maintained in minimal essential medium (MEM) comprising 10% fetal bovine serum, 2 mM L-glutamine, 1 × nonessential amino acids, 1 × MEM vitamins, 25 μg/mL gentamicin, and 1 μg/mL fungizone [19].…”
Section: Methodsmentioning
confidence: 99%
“…Direct PCR and direct qPCR eliminate the purification step, significantly shortening the protocol, but the inhibitory effect of the direct sample can be present. Previously, direct qPCR methods have been successfully applied to monitor Chlamydia and herpes simplex virus-2 growth and the antimicrobial effects of various compounds [6][7][8][9][10][11]. In this study, we want to leave out the DNA purification step and develop a direct qPCR detection method that is suitable to detect Mycoplasma contamination within U937 cell cultures.…”
Section: Introductionmentioning
confidence: 99%